Analysis of the Role of Peer Companions With Level of ARV Therapy Compliance in People Living with HIV in the Polyclinic CST Banyuwangi Regency - Suci Anggraeni; Turiatin (Universitas STRADA Indonesia, 2026)
Adherence of people living with HIV (PLWHA) to antiretroviral (ARV) therapy is a key factor in successful treatment, preventing drug resistance, and improving their quality of life. Adherence remains a challenge for people living with HIV, influenced by psychological and social factors, stigma, medication side effects, and a lack of ongoing support. The role of peer mentors is crucial as a form of social support based on shared experiences, which can increase motivation, confidence, and openness among people living with HIV (PLWHA) in undergoing therapy. The aim of this study was to analyze the role of peer companions in the level of adherence to ARV therapy among PLWHA at the CST polyclinic. This research uses a correlational research design with a cross-sectional approach. The sample in this study was a portion of new PLWHA patients, CST who met the inclusion criteria of 110 respondents. The sampling technique uses purposive sampling. Tools for the data collection process were questionnaires and observation sheets, then analyzed using the Che Square statistical test with α < 0.05. The research results show that almost all respondents received peer support, 173 people (93.0%) and almost all respondents in the obedient category, 169 people (90.9%). From the results of statistical tests using chi square, it was obtained that the p value was 0.000 < α = 0.05, meaning that Ho was accepted, namely that there was a relationship between the role of peer companions and the level of adherence to ARV therapy. For this reason, it is necessary for nurses to provide continuous nursing services for HIV/AIDS patients, nurses can work together with peer support groups, in providing holistic health services bio, psycho, social, spiritual so that it will improve the quality of life of HIV/AIDS patients AIDS is widespread